Investigating the impact of academic staff’s resistance to change on technology readiness: The mediating role of technology self-efficacy - Fourie , R.; Botha, P. A. (South African Journal of Higher Education, 2026)
This study examines the factors that affect technology adoption among academic staff at a South African university, focusing on resistance to change and technology self-efficacy. Its goal is to determine how educators’ attitudes towards technology affect their willingness to use new tools to improve digital literacy and adoption in educational settings. A cross-sectional survey was carried out among faculty members from various disciplines using a quantitative methodology. The results showed a significant gap between technology self-efficacy and readiness to adopt new technologies, with resistance to change being a major obstacle. The study proposes practical strategies that institutions can use to promote a culture of innovation and openness to technological advancements. It emphasises the importance of supportive frameworks encouraging staff to engage with digital tools. The study’s contributions include insights into overcoming resistance to change and enhancing technology readiness in higher education, providing valuable implications for policy-makers and educational leaders who aim to facilitate technological integration and innovation.